Sustainability and tourist behavior: a discussion in the light of Environmental Psychology - Costa, Cristiane Salome Ribeiro; Santos, Jaqueline Guimarães; Aguiar, Edvan Cruz (Revista de Administração da UFSM, 2015)
The study on tourist behavior has aroused increasing interest in the areas of consumer behavior and sustainability, since this is seen as an agent that directly influences the sustainability of the destination. In light of environmental psychology, specifically the SOR of Mehrabian and Russell (1974) model, it is understood that the tourist can be influenced by stimuli in the environment. Apprehends that environmental stimuli, represented by features and other information concerning the dimensions of sustainability, arranged in a tourist destination, corresponding to the variables that can influence the behavior of tourists. In this sense, this essay proposes to discuss the relationship between the characteristics of sustainable tourism destinations and tourist behavior. It is believed that the tourist destination can stimulate behaviors towards sustainability, provided that it can properly utilize the characteristics of the environment to inform and educate tourists, especially those related to the dimensions of sustainability. The paper also proposes a framework in an attempt to better understand the relationship discussed and subsequent empirical studies suggest that share the same intent.